دور المؤسسات الأردنية الرسمية في صنع السياسة الخارجية - الدعجه, حسن عبدالله; الحموري, منال (University of Eloued جامعة الوادي, 2020)
هدفت هذه الدراسة الى معرفة دور المؤسسات الأردنية في صنع السياسة الخارجية، وتحديدا المؤسسة المعنية بصنع السياسة الخارجية الأردنية الرسمية منها، واستخدمت الدراسة المنهج الوصفي التحليلي الذي يناسب هذا النوع من الدراسات، وقد عالجت الدراسة الأهداف الاتية: معرفة المتغيرات الذاتية لصانع القرار السياسي الأردني. وبيان دور الملك عبدالله الثاني في صنع السياسة الخارجية. الكشف عن دور رئيس الوزراء ووزير الخارجية الأردني في صنع السياسة الخارجية. والتعرف على دور مجلس الأمة الاردني في صناعة السياسة الخارجية الأردنية. وتحديد دور المؤسسة العسكرية الأردنية في صنع السياسة الخارجية. وقد توصلت الدراسة؛ الى ان صنع السياسة الخارجية الأردنية منوطة بالدرجة الأولى بالملك باعتباره رأس الدولة، حيث يستمد الملك دوره البارز في صنع السياسة الخارجية للأردن، وتحديد علاقات الأردن مع الدول العربية والدول الأجنبية، من ثوابت دستورية أعطته الصلاحيات التامة للقيام بهذا الدور، كما تقوم باقي المؤسسات الرسمية بدور تكاملي يساند الملك بعملية صنع السياسة الخارجية The role of official Jordanian institutions in making foreign policy Hasan Abdullah Al-Dajah & Manal Mahmoud Hamouri Abstract This study aimed to know the role of Jordanian institutions in making foreign policy, specifically the institution concerned with making official Jordanian foreign policy, and the study used the descriptive analytical approach that suits this type of studies, and the study addressed the following goals: Knowing the subjective variables of the Jordanian political decision maker. And clarify the role of King Abdullah II in making foreign policy. Disclosure of the role of the Jordanian Prime Minister and Minister of Foreign Affairs in making foreign policy. And get acquainted with the role of the Jordanian Parliament in making Jordanian foreign policy. And define the role of the Jordanian military in making foreign policy. The study found: Until the Jordanian foreign policy making is entrusted primarily to the king as the head of state, where the king derives his prominent role in making foreign policy for Jordan, and defines Jordan's relations with Arab and foreign countries, from constitutional principles that gave him full powers to play this role, just as other official institutions play a role Integrative supports the king in the foreign policy-making process. (Key words: institutions, foreign policy, Jordan).
The role of official Jordanian institutions in making foreign policy
مقال
Keywords: المؤسسات ، السياسة الخارجية، الأردن; institutions, foreign policy, Jordan.